1992
DOI: 10.1152/ajpregu.1992.263.3.r708
|View full text |Cite
|
Sign up to set email alerts
|

Somnogenic, pyrogenic, and anorectic activities of tumor necrosis factor-alpha and TNF-alpha fragments

Abstract: Exogenously administered tumor necrosis factor-alpha (TNF-alpha) elicits several symptoms of generalized infections such as fever, increased sleep, and anorexia. The aim of the present work was to localize these effects of TNF-alpha to specific amino acid sequences of the parent molecule by characterizing the in vivo and in vitro activities of several synthetic TNF-alpha fragments. Intracerebroventricular injection of TNF-alpha elicited dose-dependent fevers and increases in non-rapid-eye-movement sleep (NREMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 0 publications
6
65
0
3
Order By: Relevance
“…Consistent with current results, they affect each other's production and inhibition of one attenuates the sleep induced by the other (Takahashi et al, 1999. Low doses of IL1β or TNFα enhance non rapid eye movement sleep (NREMS) (Kapas et al, 1992;Krueger et al, 1984;Shoham et al, 1987;Tobler et al, 1984). Conditions associated with increases in endogenous levels of IL1β or TNFα, e.g., time-of-day (Floyd and Krueger, 1997;Taishi et al, 1998), excessive food intake or infectious disease (Toth and Krueger, 1988) promote NREMS.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with current results, they affect each other's production and inhibition of one attenuates the sleep induced by the other (Takahashi et al, 1999. Low doses of IL1β or TNFα enhance non rapid eye movement sleep (NREMS) (Kapas et al, 1992;Krueger et al, 1984;Shoham et al, 1987;Tobler et al, 1984). Conditions associated with increases in endogenous levels of IL1β or TNFα, e.g., time-of-day (Floyd and Krueger, 1997;Taishi et al, 1998), excessive food intake or infectious disease (Toth and Krueger, 1988) promote NREMS.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have demonstrated that subjects in the sleep-deprived state have impaired glucose tolerance, higher evening cortisol levels, increased sympathetic nervous system activity and a reduction in leptin secretion compared to those in the recovery state. 30 Although mechanisms underlying the association between long sleep duration and diabetes are unclear, chronic subclinical inflammation associated with visceral obesity may trigger long sleep duration and hyperglycemia due to the sleep-inducing 31 and metabolic 32 effects of pro-inflammatory cytokines, including interleukin-1 and tumor necrosis factor-a. Blood pressure gradually falls with the onset of sleep, and promptly rises after awakening.…”
Section: Discussionmentioning
confidence: 99%
“…In normal people the inflammatory cytokines tumor necrosis factor-a (TNF-a), interleukin-1b (IL-1b), and interleukin-6 (IL-6) are involved in physiological sleep regulation with a circadian pattern of secretion (25)(26)(27)(28). Decreased overall secretion of IL-6 is associated with a good night's sleep and a good sense of well-being the next day (27).…”
Section: Sleep Apnea and Inflammationmentioning
confidence: 99%